2013
DOI: 10.1111/jopr.12062
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of One‐Step vs. Two‐Step Impression Techniques on Long‐Term Accuracy and Dimensional Stability when the Finish Line is within the Gingival Sulcular Area

Abstract: When using the two-step putty-wash impression technique, pouring of the impressions may be postponed up to 30 hours; however, when using the one-step impression technique, pouring should be performed within 2 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 29 publications
4
39
1
1
Order By: Relevance
“…The results of the present study corroborate with other studies 7,[12][13] which claim that dimensional accuracy is not affected by the impression technique. Thus, the first hypothesis was rejected.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The results of the present study corroborate with other studies 7,[12][13] which claim that dimensional accuracy is not affected by the impression technique. Thus, the first hypothesis was rejected.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, impressions created with this type of elastomeric impression material can be obtained by different impression techniques [7][8] . Some authors 8,[10][11][12][13][14][15] have demonstrated that the impression technique is a critical factor which directly influences the dimensional accuracy. However, in this study, the dimensional accuracy of a partially edentulous mandibular arch is related more to the type of impression material than the impression technique 7,[16][17] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations